2002
DOI: 10.1177/107110070202300610
|View full text |Cite
|
Sign up to set email alerts
|

Distal Tarsal Tunnel Release with Partial Plantar Fasciotomy for Chronic Heel Pain: An Outcome Analysis

Abstract: This study evaluated the effectiveness of distal tarsal tunnel release with a partial plantar fasciotomy for chronic subcalcaneal pain syndrome in patients who failed nonoperative management through a retrospective review of all patients undergoing this procedure between 1994 and 1999. Distal tarsal tunnel release and a partial plantar fasciotomy were offered only to those patients with disabling heel pain and were performed under general anesthesia or ankle block. Seventy-five patients (80 heels), averaging 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
0
33
0
3
Order By: Relevance
“…The outcomes of TTR have varied, with failure rates of 4% to 56% reported (1,2,4,7), particularly in patients in whom a specific etiology could not be identified (10). We believe that these rates do not always reflect the "true" failure rate, because many studies have been of varieties of surgical release, including extensile release (11), the 4-medial ankle tunnel release (tibialis posterior, medial and lateral plantar nerves, and calcaneal nerve) (1,3,7,12,13), proximal-only TTR (2,3), distal-only TTR (6,14), selective nerve release (2,4,6,15), and shorter incisions (16). Again, only a few studies have been published and have included small numbers of patients with failed TTR, variable results, and a wide range of surgical procedures (4).…”
Section: Discussionmentioning
confidence: 90%
“…The outcomes of TTR have varied, with failure rates of 4% to 56% reported (1,2,4,7), particularly in patients in whom a specific etiology could not be identified (10). We believe that these rates do not always reflect the "true" failure rate, because many studies have been of varieties of surgical release, including extensile release (11), the 4-medial ankle tunnel release (tibialis posterior, medial and lateral plantar nerves, and calcaneal nerve) (1,3,7,12,13), proximal-only TTR (2,3), distal-only TTR (6,14), selective nerve release (2,4,6,15), and shorter incisions (16). Again, only a few studies have been published and have included small numbers of patients with failed TTR, variable results, and a wide range of surgical procedures (4).…”
Section: Discussionmentioning
confidence: 90%
“…Open partial plantar fascia release with decompression of the first branch of the lateral plantar nerve 42 (Figure 8) has shown up to 93% satisfaction in multiple studies. 3,10,42 This is the standard approach for patients who are recalcitrant to nonoperative management for at least 6 months.…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…3,10,42 This is the standard approach for patients who are recalcitrant to nonoperative management for at least 6 months. Watson et al 42 reported good or excellent results in 88% of cases without removing a heel spur. Complications of plantar fascia release include lateral column instability, pain in the calcaneal cuboid joint, and calcaneus fracture after heel spur removal.…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…In 85 patients (92 heels) with chronic disabling heel pain, distal tarsal tunnel release and partial plantar fasciotomy was done, followed by postoperative immobilization [30]. Good to excellent results were noted in 84% of patients with follow‐up evaluation (SF‐36, Foot Function Index, visual analogue scale (VAS), and general custom questionnaire) [30].…”
Section: Scientific Sessionsmentioning
confidence: 99%